Not in vain what God hath wrought amongst the Kanakas in Queensland being Report of the Queensland Kanaka Mission for the year 1903-1904 : Occasional paper no. 1 (1904)
Introduction and diary entries (Miss Young's account) re visit to Malayta by Messrs. Thomas, Caulfeild, and Abbott and Miss Young and Mrs Fricke.
Keywords: Queensland Kanaka Mission; Brethren movement -- missions -- Australia -- history